Effects of garlic and onion powder on egg production, antioxidant status and some blood parameters in chukar partridges - Harman, Halil (Journal of the Hellenic Veterinary Medical Society, 2022)
The study aimed to evaluate the effect of onion-garlic powder on egg production, antioxidant capacity and blood biochemistry in chukar partridges (Alectoris chukar). The study was conducted for 12 weeks during the laying period and a total of 240 partridges were divided into 4 groups (control, 1% onion, 1% garlic, and 1% onion and 1% garlic). The highest total antioxidant capacity, feed consumption and egg production were determined in the garlic group (P < 0.05 and P < 0.01 respectively) and the lowest egg production and feed intake was observed in the onion group. Egg production in the garlic –onion mixture group was also higher than the control and only onion group (P < 0.01). While there was no statistical difference in blood HDL, LDL, glucose, alkaline phosphatase, calcium, and phosphorus levels (P > 0.05), blood urea, ALT, AST levels were higher (P < 0.05) in the garlic group with the highest egg production and feed intake (P < 0.01) compared to the control and onion groups. Unlike many studies, the highest cholesterol levels were determined in the garlic supplemented group (P < 0.05) and the expected positive effects were not seen in onion powder.